Pelatihan Dan Pendampingan Penulisan Artikel Ilmiah Hasil Penelitian Bermuatan Pendidikan Karakter Bagi Guru Mi Se-K3MI Kecamatan Kedungkandang 1 Kota Malang - Siti Sumarsilah; Susandi Susandi; Anita Kurnia Rachman (JPM PAMBUDI, 2019)
Teachers have the obligation to write articles as a form of creativity and achievement. Writing articles better in accordance with the field of science they have. Referring to the problem of the difficulty of writing scientific articles in the Teacher Working Group in K3-MI in Kedungkandang District 1, namely the teacher has not been able to choose themes, frameworks, write paragraphs, and determine theories in writing articles. Solutions offered, namely the teacher writes articles according to interests. Before writing articles it's better to write an article framework. Paragraph compilation which is cohesion and coherence. Theory for strengthening ideas and ideas. The method used aims to produce skills in writing articles. This stage includes discussion of work plans, training activities include the provision of theoretical and practical material, with a composition of 30% theory and 70% practice. Article writing activities are carried out with guidance. Program evaluation and monitoring to provide solutions to problems. Skill improvement for participants is in accordance with experiential learning theory. The trainees who are increasingly active in the training activities, the more knowledge they have because the more information they get. The conclusion of this activity is that teachers are better off writing articles according to their interests. Before writing an article it would be better to write a framework. Good writing is generated from the preparation of paragraphs that are cohesion and coherence. Theory is needed to strengthen ideas and ideas in writing.